Determinants for early introduction of complementary foods in Australian infants: findings from the HSHK birth cohort study - Arora, Amit; Manohar, Narendar; Hector, Debra; Bhole, Sameer; Hayen, Andrew; Eastwood, John G; Scott, Jane (BioMed Central, 2020)
Objective: The purpose of this study was to examine the timing of introduction of complementary (solid) foods among infants in South Western Sydney, Australia, and describe the maternal and infant characteristics associated with very early introduction of solids.